MODIFIED CARBON PASTE ELECTRODE WITH TITANIUM(IV) OXIDE NANOPARTICLE FOR VOLTAMMETRIC ANALYSIS OF CAFFEINE - Tiffanny Devi Salsabila, Nadia
Consumption of excess caffeine can cause bad side effects for health. For this reason, daily caffeine consumption must be below the maximum limit is 400 mg per day. Various methods have been developed to determine caffeine content, voltammetric method is one of simple working method and low cost. The working electrode can be modified to provide better measurements. Titanium(IV) oxide nanoparticles can be used as a modifier of carbon paste electrodes (CPE) because they are cheap, have electrocatalytic properties, and can increase the sensitivity of the working electrode. CPE was modified using titanium(IV) oxide nanoparticles was carried out in this study for voltammetric analysis of caffeine content to increase the sensitivity of CPE. The synthesis of titanium(IV) oxide nanoparticles produced a material with a size of 220.4 ± 3.90 nm. However, the titanium(IV) oxide nanoparticles modified CPE (CPE-TNPs) was proven to increase the oxidation current of 1 mM caffeine standard solution from 14.1 ± 0.6 ?A to 20.2 ± 1.0 ?A. The analysis was carried out using a square wave voltammetry (SWV) technique in the range of 1.0 – 1.8 V, scan rate of 125 mV.s-1, with 0.1 M H2SO4 solution as an electrolyte solution, and the composition of titanium(IV) oxide nanoparticles in the modified CPE is 3% (w/w). The synthesized CPE-TNPs had a fairly good repeatability and repoducibility. In addition, the modified CPE also has a linear region in the range of 30-100 ?A and 100-500 ?A with a detection limit of 12.01 ?M. Modified CPE was also used to measure caffeine content in beverage samples and showed a recovery percentage of 107.62±1.01%.